1967
DOI: 10.1037/h0025116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discrimination training on stimulus generalization for human subjects.

Abstract: 3 groups of 15 human Ss each were given wavelength discrimination training to respond to the S+ (530 m/t) but not to S-(540 m/i, 550 rnfi, and 590 m/t, respectively). A 4th (control) group (n=15) received instructions to respond only to S+ but no discrimination training. All Ss were then tested for generalization to wavelengths on both sides of the S+. Relative to the control gradient, both the 540 m/j S-and 550 m/t S-groups showed displacement of the mode of responding from S+ in the direction opposite to S-.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
46
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 9 publications
6
46
0
Order By: Relevance
“…But Thomas (1974) has emphasized that the adaptation-level model may be the more appropriate one for understanding human discrimination learning. In support of Thomas' claim, two experiments with human subjects have found direct relationships between stimulus differences and amount of shift (Doll & Thomas, 1967;Thomas, Svinicki, & Vogt, 1973). However, Baron (1973), using comparable procedures, found that gradient displacements were inversely related to differences between the positive and negative stimuli on the auditory frequency dimension with human subjects.…”
mentioning
confidence: 84%
“…But Thomas (1974) has emphasized that the adaptation-level model may be the more appropriate one for understanding human discrimination learning. In support of Thomas' claim, two experiments with human subjects have found direct relationships between stimulus differences and amount of shift (Doll & Thomas, 1967;Thomas, Svinicki, & Vogt, 1973). However, Baron (1973), using comparable procedures, found that gradient displacements were inversely related to differences between the positive and negative stimuli on the auditory frequency dimension with human subjects.…”
mentioning
confidence: 84%
“…Moreover, the generality of the peak-shift effect has been extended to a variety of stimulus dimensions, including visual intensity (Ernst, Engberg, & Thomas, 1971), auditory intensity (Thomas & Setzer, 1972), line tilt (Bloomfield, 1967), floor tilt (Riccio, Urda, & Thomas, 1966), object size (Dougherty & Lewis, 1991), and even relative numerosity (Honig & Stewart, 1993). The effect has also been extended to various species including goldfish (Ames & Yarczower, 1965), rats and guinea pigs (Thomas & Setzer, 1972), chickens (Rudolph & Honig, 1972), horses (Dougherty & Lewis, 1991), and humans (Doll & Thomas, 1967). Thus, the peak-shift effect appears to be a reliable and general result of intradimensional discrimination training, although individual differences do exist, and some individuals fail to show the effect (see Honig & Urcuioli, 1981;Rilling, 1977;Purtle, 1973, for reviews).…”
mentioning
confidence: 99%
“…The extensive literature on this shift phenomenon in animals has been reviewed by Purtle (1973), and studies of peak shift in humans have been reviewed by Thomas (1974). In the first study with human subjects, Doll and Thomas (1967) used a monochromatic light of 530 nm as S+ and one of 550 nm as S-, with trial-by-trial feedback on correctness. Subse-quent generalization testing without feedback revealed a gradient that peaked at 520 run.…”
mentioning
confidence: 99%